Exhibition artillery drill, military athletic tournament, Alaska Yukon Pacific Exposition, Seattle, June 1909. - Rognon, Orville J. (1909)
On verso of image: Fourth Field Artillery, Mountain Battery, ready for action. PH Coll 779.9 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number